Ammonium Glycyrrhizinate and Bergamot Essential Oil Co-Loaded Ultradeformable Nanocarriers: An Effective Natural Nanomedicine for In Vivo Anti-Inflammatory Topical Therapies - Maria Chiara Cristiano; Nicola d’Avanzo; Antonia Mancuso; Martine Tarsitano; Antonella Barone; Daniele Torella; Donatella Paolino; Massimo Fresta (Biomedicines, 2022)
Bergamot essential oil (BEO) and Ammonium glycyrrhizinate (AG), naturally derived compounds, have remarkable anti-inflammatory properties, thus making them suitable candidates for the treatment of skin disorders. Despite this, their inadequate physicochemical properties strongly compromise their topical application. Ultradeformable nanocarriers containing both BEO and AG were used to allow their passage through the skin, thus maximizing their therapeutic activity. Physicochemical characterization studies were performed using Zetasizer Nano ZS and Turbiscan Lab®. The dialysis method was used to investigate the release profile of the active compounds. In vivo studies were performed on human healthy volunteers through the X-Rite spectrophotometer. The nanosystems showed suitable features for topical cutaneous administration in terms of mean size, surface charge, size distribution, and long-term stability/storability. The co-delivery of BEO and AG in the deformable systems improved both the release profile kinetic of ammonium glycyrrhizinate and deformability properties of the resulting nanosystems. The topical cutaneous administration on human volunteers confirmed the efficacy of the nanosystems. In detail, BEO and AG-co-loaded ultradeformable vesicles showed a superior activity compared to that recorded from the ones containing AG as a single agent. These results are promising and strongly encourage a potential topical application of AG/BEO co-loaded nanocarriers for anti-inflammatory therapies.